CHANGES OF ORGANOMETRIC PARAMETERS OF WHITE RATS SPLEEN UNDER CONDITIONS OF INDUCED ONCOGENESIS IN DYNAMICS OF EXPERIMENT - Lisnychuk, N.; Andriichuk, I.; Soroka, Yu. (World of Medicine and Biology, 2017)
The changes in mass and organometric indices of the spleen of nonlinear white rats under conditions of DMG-induced oncogenesis have been experimentally investigated. A progressive decrease in the body weight of experimental animals with a neoplastic process was found. A significant decrease in both the mass and spatial characteristics of the spleen in the dynamics of the experiment has been established. The determination of the pathogenic mechanisms of organometric changes in the spleen under conditions of an experimentally modeled neoplastic process requires further histological examination of changes in the structural components of the organ.
Keywords: Mass and organometric parameters; spleen; еxperimental oncogenesis; white rats